Pemanfaatan Fermentasi Tumpi Jagung Sebagai Alternatif Ketersediaan Pakan Ternak di Desa Keli Kecamatan Woha - Oscar Yanuarianto; Dedy Supriadin; M. Ridwan Saidi; Ryan Aryadin Putra; Burhan Burhan (Jurnal Gema Ngabdi, 2023)
Counseling on “Utilization of Corn Tumpi Fermentation as an Alternative for Availability of Livestock Feed in Keli Village, Woha Sub-district, was held in September involving farmers, especially those who raise cattle and goats in Keli Village, Woha District, Bima Regency. Another target is the general public who want to know and need knowledge in the fermentation of corn tumpi in animal feed. This activity was carried out through counseling and discussion as well as short training through demonstrations and practices on the manufacture of fermented corn tumpi. This counseling involved more than 29 participants from the planned 20 participants and also involved 6 final semester students. The results of the extension showed that the extension participants were very enthusiastic about the training material, which could be seen from their active participation in all activities, especially during discussion and practice sessions and increasing understanding of the benefits and technology of corn tumpi fermentation as animal feed